Studi Awal Geologi di Daerah Beruang Kanan Kabupaten Gunung Mas Propinsi Kalimantan Tengah - Retno Anjarwati; Arifudin Idrus; Lucas Donny Setijadji (PROMINE, 2018)
The regional tectonic conditions of the KSK Contract of Work are located in the mid-Tertiary magmatic arc (Carlile and Mitchell, 1994) which host a number of epithermal gold deposits (eg, Kelian, Indon, Muro) and significant prospects such as Muyup, Masupa Ria, Gunung Mas and Mirah. Copper-gold mineralization in the KSK Contract of Work is associated with a number of intrusions that have occupied the shallow-scale crust at the Mesozoic metamorphic intercellular junction to the south and continuously into the Lower Tertiary sediment toward the water. This intrusion is interpreted to be part of the Oligocene arc of Central Kalimantan (in Carlile and Mitchell 1994) Volcanic rocks and associated volcanoes are older than intrusions, possibly aged Cretaceous and exposed together with all three contacts (Carlile and Mitchell, 1994) some researchers contribute details about the geological and mineralogical background, and some papers for that are published for the Beruang Kanan region and beyond but no one can confirm the genesis type of the Beruang Kanan region The mineralization of the Beruang Kanan area is generally composed by high yields of epithermal sulphide mineralization. with Cu-Au mineralization This high epithermal sulphide deposition coats the upper part of the Cu-Au porphyry precipitate associated with mineralization processes that are generally controlled by the structure